On the large deviations for the densities - Saulis, L. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. И. Саулис. О больших уклонениях для плотностей L. Saulis. Apie didelius nukrypimus tankiams